Treatment persistence and maintenance dose titration among ulcerative colitis patients on biologics: a pooled study of three United States claim databases. (3rd July 2022) - Sah, Janvi; Teeple, Amanda; Muser, Erik; Gutierrez, Cynthia; Dassopoulos, Themistocles
Abstract: Objective: This real-world study evaluated biologic treatment patterns in patients with moderate-to-severe ulcerative colitis (UC). Methods: IQVIA PharMetrics, IBM MarketScan, and Optum Clinformatics were pooled to identify UC patients with ≥1 claim for UC and ≥1 claim for adalimumab (ADA), golimumab (GOL), infliximab (IFX), or vedolizumab (VDZ). The index date for each biologic was the first claim for that biologic. Patients could be included in >1 cohort if they switched biologics during the identification period. Continuous eligibility for medical/pharmacy benefits was required for 12 months before (baseline) and after (follow-up) the index date. Patients lacking claims for any biologic during baseline were categorized as bio-naïve; those with any biologic claim were categorized as bio-experienced. Persistence was defined as the proportion of patients that remained on the index biologic without a gap between claims of >28 days for ADA, >56 days for GOL, and >112 days for IFX and VDZ. Dose titration was assessed among patients with ≥2 maintenance doses during follow-up among ADA, GOL, and VDZ patients. Results: In total, 6, 106 bio-naïve UC patients and 1, 027 bio-experienced UC patients were identified. Patients treated with VDZ and IFX had the highest persistence followed by ADA and GOL patients for bio-naïve and bio-experienced, respectively. ADA patients had a numerically higher proportion of patients with 50% dose escalation, followed by VDZ and GOL; 50% dose reduction was observed in ≤1% patients. Conclusions: In this descriptive study of UC patients without confounder adjustment, VDZ persistence was numerically highest followed by IFX, GOL, and ADA across both populations.